S SPACE AGRICULTURE: what is it? - Squizatti, Lucas (Revista Interface Tecnológica, 2022)
The present work aims, throughout its contents, to promote the understanding of space agriculture, as it has been developing over time. The general objective of the research is to describe the main aspects related to space agriculture, regarding the specific objectives, they are: to evaluate the development of agriculture within the space environment; highlight the main agricultural activities; to emphasize the methodology adopted with the agricultural process in view of the demographic environment. Agriculture can be considered one of the main activities promoted within the economic environment, having a view of processes or procedures that can be inserted into the production routine. In the methodological process, a literature review was carried out, promoting a highlight of the main concepts related to the theme, as well as an assessment of which resources or processes are applied in space agriculture. It can be evaluated from the contents presented that over the years agricultural activities have been applied in different environments, granting an effectiveness and application of agriculture in different regions or environments.
Keywords: Agriculture; space; Resources